Synergistic Influences of Doping Techniques and Well‐Defined Heterointerface Formation to Improve the Photocatalytic Ability of the S‐ZnO/GO Nanocomposite. Issue 29 (3rd August 2022) - Javed, Mohsin; Qamar, Muhammad Azam; Iqbal, Shahid; Aljazzar, Samar O.; Iqbal, Sadia; Khan, Humaira; Abourehab, Mohammed A. S.; Elkaeed, Eslam B.; Alharthi, Abdulrahman I.; Awwad, Nasser S.; Ibrahium, Hala A.
Abstract: Environmental pollutants such as organic dyes are major focal areas of the current era. For this reason, excellent photocatalytic substances are needed time to degrade such water bodies and get pollution‐free water. In this study, Sulphur doped zinc oxide nanoparticles were fabricated utilizing a solution‐free technique, while graphene oxide was synthesized using a modified hummer's method. Sulphur‐doped zinc oxide nanoparticles were mixed with graphene oxide in five distinct weight percentages to achieve the S‐ZnO/GO (SZO) composites. The 8 % SZO NC demonstrated superior photocatalytic efficiency, degrading 100 % of MB in 110 minutes under sunlight irradiation. The synthesized composites were characterized by the techniques viz. TEM, SEM, EDXS, FTIR, XPS, and UV spectrophotometry to determine their chemical nature and morphological features. Methylene blue was used as a reference pollutant to evaluate the photocatalytic activity of the composites. According to the radical scavenger's test observations, OH and O 2– were the primary species responsible for MB decomposition. Furthermore, the nanocomposites were found highly stable, with a continuously high degree of dye degradation throughout six catalytic cycles. As a result, the SZO nanocomposites have the prospective to be an extremely effective and versatile photocatalyst for the photodegradation of organic wastes. Abstract : A solution‐free method was used to create S‐ZnO NPs, while a modified hummer's method was used to make GO. The surface area of S‐ZnO NCs is increased by the efficient adsorption of S‐ZnO NPs on fragile GO sheets. In terms of photocatalytic activity, recyclability, and stability, the newly constructed S‐ZnO composite was better than individual S‐ZnO NPs and GO sheets. This research provided an easy method for creating S‐ZnO/GO nanocomposites for use in environmental areas.